Pembuatan Direktori Naskah Kuno Khusus Hikayat Minangkabau di Museum Adityawarman - Suri, Anggun; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about how special Manuscript Preparation Tale Directory Minangkabau in Adityawarman Museum. Writing paper aims to describe the process of making a special codex directory Minangkabau at the Adityawarman Museum. The method used is descriptive method performed by field observations, interviews, and collect data directly from the original source, which is a special collection of ancient manuscripts at the Museum contained Adityawarman. Based on the discussion can be concluded the stage of making a directory codex Minangkabau Museum Adiyawarman are as follows : (1) the collection of ancient manuscripts specifically saga Minangkabau, (2) details of the number of ancient manuscripts specifically saga Minangkabau, (3) how the preparation in the manufacture directory codex special Minangkabau. The constraints in the manufacturing directory Minangkabau codex saga is as follows: (1) the title of the manuscript is unknown, (2) the manuscript ready unknown author, (3) difficult determine how many pages of ancient manuscripts Minangkabau.       Keyword: manuscript, Minangkabau, Museum Adiyawarman